Prediksi dan Pencegahan Risiko Burnout pada Pekerja Fleksibel Menggunakan Algoritma Random Forest - Fauziah Mk, Noha Noor; Hakim, Dimas Lukman; Cahyani, Ainun; Sariasih, Findi Ayu; Rakhmah, Syifa Nur; Sutoyo, Imam (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Flexible workers operating under remote, hybrid, and freelance schemes face burnout risks that are difficult to detect early due to irregular work patterns and blurred work-time boundaries. Conventional burnout monitoring relying on manual surveys is static and lacks sensitivity to the dynamics of workers' psychological changes. This study aims to develop a machine learning-based burnout prediction system for flexible workers capable of providing real-time risk predictions accompanied by personalized prevention recommendations. The method employed is Random Forest Classifier using a dataset from Kaggle titled